The Effects of Plant Fibers on Improving the Properties of Meat Emulsion - KURT, Ş.; CEYLAN, H.G. (Journal of the Hellenic Veterinary Medical Society, 2020)
The effects of plant fibers (1%; pea, wheat, apple, carrot, lemon, oat, inulin, cellulose) on the emulsion stability (ES), capacity (EC), density (ED), activity (EA), viscosity (EV) and apparent yield stress of emulsion (AYSe) and emulsion gel (AYSg) of beef were studied using a model system. The fibers had significant (p<0.05) effect on the emulsion properties. Apple and lemon fibers increased EA values and addition of carrot and wheat fibers increased ED values. Carrot, lemon and oat fibers increased ES values while lemon fiber increased emulsion storage stability the most. Inulin and apple fibers decreased AYSe values while other fibers increased. AYSg values increased with the addition of wheat fiber, but decreased with the addition of other fibers. However, the fibers did not significantly (p>0.05) improve emulsion capacity. On the other hand, the added fibers improved the emulsion viscosity.